Interleukin-1 and cancer progression: the emerging role of interleukin-1 receptor antagonist as a novel therapeutic agent in cancer treatment - Varghese Sheelu; Lewis Anne M; Xu Hui; Alexander H Richard (Journal of Translational Medicine, 2006)
Abstract The tumor microenvironment consists of tumor, immune, stromal, and inflammatory cells which produce cytokines, growth factors, and adhesion molecules that promote tumor progression and metastasis. Of particular interest in this setting is interleukin-1 (IL-1), a pleiotropic cytokine with numerous roles in both physiological and pathological states. It is known to be up regulated in many tumor types and has been implicated as a factor in tumor progression via the expression of metastatic and angiogenic genes and growth factors. A number of studies have reported that high IL-1 concentrations within the tumor microenvironment are associated with a more virulent tumor phenotype. Solid tumors in which IL-1 has been shown to be up regulated include breast, colon, lung, head and neck cancers, and melanomas, and patients with IL-1 producing tumors have generally bad prognoses. The exact mechanisms by which IL-1 promotes tumor growth remain unclear, though the protein is believed to act via induction of pro-metastatic genes such as matrix metalloproteinases and through the stimulation of adjacent cells to produce angiogenic proteins and growth factors such as VEGF, IL-8, IL-6, TNFα, and TGFβ. The IL-1 receptor antagonist (IL-1ra) is a naturally occurring inhibitor to IL-1 and acts by binding to the IL-1 receptor without activating it. The protein has been shown to decrease tumor growth, angiogenesis, and metastases in murine xenograft models. Our focus in this review is to summarize the known data on the role of IL-1 in tumor progression and metastasis and the use of IL-1 inhibition as a novel therapeutic approach in the treatment of solid organ malignancies.